2015
DOI: 10.1038/jcbfm.2015.83
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Kv7 Channels in Oxygen and Glucose Deprivation-Induced Damage in Rat Caudate Brain Slices

Abstract: Ischemic stroke can cause striatal dopamine efflux that contributes to cell death. Since K v 7 potassium channels regulate dopamine release, we investigated the effects of their pharmacological modulation on dopamine efflux, measured by fast cyclic voltammetry (FCV), and neurotoxicity, in Wistar rat caudate brain slices undergoing oxygen and glucose deprivation (OGD). The K v 7 activators retigabine and ICA27243 delayed the onset, and decreased the peak level of dopamine efflux induced by OGD; and also decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…In addition, we found that the addition of the auxiliary subunit KCNE2 decreased the retigabine sensitivity of heterotetrameric K V 7.2-K V 7.3, but not of K V 2.1, channels. These findings identify K V 2.1 as an important molecular target for the action of retigabine and, due to K V 2.1’s key role in apoptosis, could help explain the previously reported neuroprotective properties 24 25 26 .…”
supporting
confidence: 63%
See 2 more Smart Citations
“…In addition, we found that the addition of the auxiliary subunit KCNE2 decreased the retigabine sensitivity of heterotetrameric K V 7.2-K V 7.3, but not of K V 2.1, channels. These findings identify K V 2.1 as an important molecular target for the action of retigabine and, due to K V 2.1’s key role in apoptosis, could help explain the previously reported neuroprotective properties 24 25 26 .…”
supporting
confidence: 63%
“…Therefore, retigabine might prevent apoptosis through inhibition of K V 2.1 currents, thus promoting cell survival. However, retigabine was found to promote neuroprotection by diminishing excitotoxicity through suppression of hyperexcitability by K V 7 channel activation 24 25 26 . Thus, retigabine might promote neuroprotection in neurons through its concerted action on K V 2 and K V 7 channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluctuations of this current under pathological states [49][50][51] may contribute to SD susceptibility, and serve as a therapeutic target in epilepsy and other neurological disorders…”
Section: Discussionmentioning
confidence: 99%
“…Brain tissue hypoxia, ischemia, and metabolic disorders not only directly participate in the process of brain injury, but also work together with other secondary injury mechanisms to aggravate brain tissue damage. (2). And NO, ET and ICP also play an important biological activity in acute cerebral ischemia, and participate in the occurrence and development of cerebral infarction.…”
Section: Introductionmentioning
confidence: 99%